Estimation of Slip Distribution of the 2007 Bengkulu Earthquake from GPS Observations Using the LeastSquares Inversion Method - Irwan Meilano; Sri Widiyantoro; Moehammad Awaluddin (Journal of Engineering and Technological Sciences, 2012)
Continuous  Global  Positioning  System  (GPS)  observations  showed significant  crustal  displacements  as  a  result  of  the  Bengkulu  earthquake occurring on September 12, 2007. A maximum horizontal displacement of 2.11 m was observed at PRKB station, while the vertical component at BSAT station was lifted up with a maximum of 0.73 m, and the vertical component at LAIS station had subsided  "“0.97 m. Adding more constraints on the inversion for the Bengkulu earthquake slip distribution inferred from GPS observations can help solve  the  underdetermined  least-squares  inversion.  Checkerboard  tests  were performed  to  help  conduct  the  weighting  for  constraining  the  inversion.  The inversion calculation yielded an optimal value for the slip distribution by giving the smoothing constraint a weight of 0.001 and the slip constraint a weight of = 0 at the edge of the earthquake rupture area. The maximum co-seismic slip of the optimal inversion calculation was 5.12 m at the lower area of PRKB station and BSAT station. The seismic moment calculated from the optimal slip distribution was 7.14 x 1021 Nm, which is equivalent to a magnitude of 8.5.